Agreement of aptamer proteomics with standard methods for measuring venous thrombosis biomarkers. Issue 4 (4th May 2021) - Faquih, Tariq; Mook‐Kanamori, Dennis O.; Rosendaal, Frits R.; Baglin, Trevor; Willems van Dijk, Ko; van Hylckama Vlieg, Astrid
Abstract: Background: Venous thromboembolism (VTE) is a complex disease with an incidence rate of about 1 in 1000 per year. Despite the availability of validated biomarkers for VTE, unprovoked events account for 50% of first events. Therefore, emerging high‐throughput proteomics are promising methods for the expansion of VTE biomarkers. One such promising high‐throughput platform is SomaScan, which uses a large library of synthetic oligonucleotide ligands known as aptamers to measure thousands of proteins. Objective: The aim of this study was to evaluate the viability of the aptamer‐based SomaScan platform for VTE studies by examining its agreement with standard laboratory methods. Methods: We examined the agreement between eight established VTE biomarkers measured by SomaScan and standard laboratory immunoassay and viscosity‐based instruments in 54 individuals (27 cases and 27 controls) from the Thrombophilia, Hypercoagulability and Environmental Risks in Venous Thromboembolism study. We performed the agreement analysis by using a regression model and predicting the estimates and the 95% prediction interval (PI) of the laboratory instrument values using SomaScan values. Results: SomaScan measurements exhibited overall poor agreement, particularly for D‐dimer (average fit, 492.7 ng/mL; 95% PI, 110.0‐1998.2) and fibrinogen (average fit, 3.3 g/L; 95% PI, 2.0‐4.7). Conclusion: Our results indicate that SomaScan measurement had poor agreement with the standard laboratory measurements. These results may explain why some genome‐wide association studies with VTE proteins measured by SomaScan did not confirm previously identified loci. Therefore, SomaScan should be considered with caution in VTE studies.